A descriptive study of learning processes and outcomes in two problem-based curriculum designs. - Solomon PE; Binkley J; Stratford PW (Journal of Physical Therapy Education (American Physical Therapy Association, Education Section))
This descriptive study presents learning processes and outcomes for students from two different problem-based curricula as they studied a health care problem. Students from a more classical, integrated problem-based curriculum and students from transitional curriculum generated similar issues for self-study. An integrated curriculum is defined as one that is problem based from the outset. There are no subject-related courses, and the majority of the content is introduced via problems, with the problem-based tutorial being the major integrative educational event. A transitional curriculum is defined as one that commences with a traditional subject-based curriculum and gradually move toward a problem-based format as students progress through the curriculum. The students from the integrated curriculum spent more time searching for information in self-directed study and used a greater variety of resources. The students from the transitional curriculum were more satisfied with both their group's performance and their own performance. Scores on multiple-choice examinations were essentially the same for both groups. Both integrated and transitional curriculum designs are viable alternatives for physical therapy educators. This study highlights potential advantages and disadvantages of each.